The psychosocial implication of childhood constipation on the children and family: A scoping review protocol. [version 2; peer review: 2 approved, 1 approved with reservations] - Yvonne McCague; Suja Somanadhan; Eileen Furlong; Diarmuid Stokes (HRB Open Research, 2024)
Background Constipation is a common problem in childhood that can have psychological, emotional, social, and health-related quality-of-life (HRQOL) consequences on children and their families. Primary or functional constipation (FC) has no known underlying pathology but is associated with lifestyle, psychological, and behavioural factors. Misdiagnosis and inadequate management of constipation can result in chronicity that can continue to adulthood, reducing quality of life for the child and their parents/family. It also causes emotional, psychological and emotional distress and concern for children and their families. This scoping review aims to answer the research question, “What has been reported about the psychosocial implication of childhood constipation among children and their families?” Methods The methodology for this scoping review will draw on the six stages of Arksey and O’Malley Framework and the updated and refined version by Peters et al. (2022). The process and reporting will follow the PRISMA-ScR guidelines. The Population, Concept and Context (PCC) framework will guide the development of inclusion criteria and the search strategy for this scoping review. Systematic literature searches of PUBMED, CINAHL, ASSIA, PsycInfo and Cochrane Library will be conducted from inception to present. The critical appraisal will be performed on selected articles to promote trustworthiness and methodological rigour. Plans for consultation exercise and dissemination of findings will also be presented. Conclusion This scoping review aims to present a comprehensive synthesis of the characteristics and extent of available literature to develop an understanding of and identify gaps in current knowledge regarding the psychosocial implication of childhood constipation on children and their families.